1998
DOI: 10.1021/la980582m
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Kinetics of Particles at a Solid Surface Governed by the Ballistic Deposition Model

Abstract: The deposition kinetics of polymeric microspheres (average diameter 8.742 µm, density 1.50 g‚cm -3 ) on smooth silica plates was determined experimentally. The measurements were carried out in a sedimentation cell using a direct microscope observation technique supplemented by the image analysis. The experimental data were interpreted in terms of the ballistic deposition (BD) model, where the irreversibility of the adsorption is assumed. It was found that both deposition kinetics and the jamming coverage (dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…These were slightly more rapid than predicted by the BD model . These results were, however, not confirmed by recent experiments performed by Carl et al who found good agreement between the experimental data and the BD model predictions. These results seem thus to confirm that the ballistic deposition model can be used as a first approximation to describe both the structure of irreversibly deposited layers under the strong influence of gravity and the adsorption kinetics.…”
Section: Influence Of the Gravity On The Adsorption/deposition Processcontrasting
confidence: 77%
“…These were slightly more rapid than predicted by the BD model . These results were, however, not confirmed by recent experiments performed by Carl et al who found good agreement between the experimental data and the BD model predictions. These results seem thus to confirm that the ballistic deposition model can be used as a first approximation to describe both the structure of irreversibly deposited layers under the strong influence of gravity and the adsorption kinetics.…”
Section: Influence Of the Gravity On The Adsorption/deposition Processcontrasting
confidence: 77%
“…To describe irreversible adsorption kinetics and the structure of the layers formed by deposited objects (usually spherical particles), various models can be considered. The most popular model on a 2D surface is the random generalized sequential adsorption (RSA) model, which has recently received many extensions such as reversible desorption and surface mobile particles. , The RSA model assumes the deposition of monodisperse and hard circles on a surface having periodic boundary conditions. The x , y positions of the circle centers are chosen randomly at the deposition plane.…”
Section: Introductionmentioning
confidence: 99%